Review on Prevalence and risk fa Review on Prevalence and risk factors of Eimeria species in Buffaloes - Makawi, zainab A. (Al-Qadisiyah Journal of Pure Science, 2021)
Abstract The research was performed in order to investigate the prevalence of Eimeria spp in buffalo. Coccidiosis, is a common livestock disease include water buffaloes and nothing is known about the most pathogenic species of Eimeria. Since the highest prevalence of oocyst shedding and incidence of disease occurs in buffalo calves less than one year of age. The omnipresent occurrence and negative effects of the infection on health and buffalo growth output are taken into account. Therefore, both farmers and veterinarians should pay greater attention to infections with Eimeria spp. And there is little analysis of data reported in Iraq and the world regarding Eimeria infection in river buffalo spp.